Does loneliness make people interested with other people in Instagram? The moderating role of loneliness in envy and fear of missing out - Yundianto, Devie; Khatami, Muhammad (Jurnal Psikologi, 2024)
Background: Envy could worsen fear of missing out (FoMO) by encouraging comparison with others via social media use. Studies also found that loneliness could further increase individual's activeness on social media and shifting face-to-face social activities. Purpose: This research aims to test the moderating role of loneliness in envy and fear of missing out.Method: 538 respondents aged 18-34 years who use Instagram participated by completing Benign Envy Malicious Scale (BEMAS), UCLA Loneliness Scale, and FoMO scale. The data obtained is then analyzed by moderation regression testing with the following models: 1) Envy and Loneliness Model, 2) Envy, Loneliness, and moderator (Envy x Loneliness). Findings: The results show that envy, t(535) = 8.523, p < .001, and loneliness, t(535) = 2.389, p < .001, have a positive influence on FoMO. Furthermore, loneliness is proven to partially moderate the relationship between envy and FoMO, which gives the buffering effect on the relationship; results presented in the article. This finding happened because there are factors for self-exclusion of individuals when experiencing loneliness. Implication: Further research is suggested to look in the opposite direction from Envy towards FoMO to FoMO against Envy, and this is done to see if jealous behavior is caused by FoMO, which envy can cause mental problems for most individuals.